Testing a new listening-room - LANGVARD, Bjarne; MØLLER, Henrik; BUDZYŃSKI, Gustaw (Archives of Acoustics, 1989)
New listening-rooms purposely designed and built are relatively seldom described in the literature, nevertheless problems arise especially when assessing their acoustic quality. Such problems are considered on the example of a new listening-room of the Acoustic Laboratory at the Aalborg University in Denmark. Results of the measurements and testing are discussed and some more general conclusions presented.